Characterization of the transcriptome of fast and slow muscle myotomal fibres in the pacu (Piaractus mesopotamicus) - Mareco, Edson Assunção [UNESP] (2015)
Background: The Pacu (Piaractus mesopotamicus) is a member of the Characiform family native to the Prata Basin (South America) and a target for the aquaculture industry. A limitation for the development of a selective breeding program for this species is a lack of available genetic information. The primary objectives of the present study were 1) to increase the genetic resources available for the species, 2) to exploit the anatomical separation of myotomal fibres types to compare the transcriptomes of slow and fast muscle phenotypes and 3) to systematically investigate the expression of Ubiquitin Specific Protease (USP) family members in fast and slow muscle in response to fasting and refeeding.Results: We generated 0.6 Tb of pair-end reads from slow and fast skeletal muscle libraries. Over 665 million reads were assembled into 504,065 contigs with an average length of 1,334 bp and N50 = 2,772 bp. We successfully annotated nearly 47% of the transcriptome and identified around 15,000 unique genes and over 8000 complete coding sequences. 319 KEGG metabolic pathways were also annotated and 380 putative microsatellites were identified. 956 and 604 genes were differentially expressed between slow and fast skeletal muscle, respectively. 442 paralogues pairs arising from the teleost-specific whole genome duplication were identified, with the majority showing different expression patterns between fibres types (301 in slow and 245 in fast skeletal muscle). 45 members of the USP family were identified in the transcriptome. Transcript levels were quantified by qPCR in a separate fasting and refeeding experiment. USP genes in fast muscle showed a similar transient increase in expression with fasting as the better characterized E3 ubiquitin ligases.Conclusion: We have generated a 53-fold coverage transcriptome for fast and slow myotomal muscle in the pacu (Piaractus mesopotamicus) significantly increasing the genetic resources available for this important aquaculture species. We describe significant differences in gene expression between muscle fibre types for fundamental components of general metabolism, the Pi3k/Akt/mTor network and myogenesis, including detailed analysis of paralogue expression. We also provide a comprehensive description of USP family member expression between muscle fibre types and with changing nutritional status.